Ridge-to-reef conservation avoids future deforestation and sediment exposure of coral reefs - Dominic Muenzel; Eleanor Stewart; Noviar Andayani; Alex J. Dumbrell; Jamaluddin Jompa; Gino Limmon; Jatna Supriatna; Johny S. Tasirin; Nurul L. Winarni; Zuliyanto Zakaria; Zoe G. Davies; Matthew J. Struebig; et al. (Biological Conservation, 2026)

Optimising site selection for ecosystem approaches to shrimp aquaculture in mangrove systems - Dominic Muenzel; Aji W. Anggoro; Dewi Embong Bulan; Yadi; Nurfadilah; Rahadian Pratama; Muhammad Ilman; Basir; Mariski Nirwan; Vabian Adriano; Muhammad M. Bayyan; Topik Hidayat; et al. (Aquaculture International, 2025)
Indonesia has experienced significant mangrove loss due to aquaculture expansion, particularly for shrimp farming, leading to the degradation of habitats and critical ecosystem services such as carbon storage, coastal protection, and fish spawning grounds. Ecosystem based aquaculture approaches offer a pathway to both mitigate environmental impacts and support sustainable seafood production. Here we explore the implementation of the Shrimp-Carbon Aquaculture (SECURE) approach in Berau Regency, East Kalimantan, Indonesia, which integrates mangrove restoration with organic shrimp farming to achieve sustainable aquaculture. Using environmental DNA (eDNA) metabarcoding to detect species from DNA shed into the environment, we assessed impacts of SECURE intervention compared to traditional ponds and found increased abundance of key taxonomic groups associated with healthy aquatic ecosystems, such as phytoplankton Chaetoceros, Chlorophyceae, and Cryptomonadales and zooplankton Calanoida and Cyclopoida. We then conducted a spatial prioritisation analysis to identify additional areas for SECURE implementation, considering mangrove restoration and protection potential, profitability, and intervention costs. High-priority ponds for restoration were typically set back from riverbanks, large, and spatially clustered, indicating opportunities for cost-effective, strategic expansion. This study underscores how spatial prioritisation can support strategic implementation of aquaculture to balance ecosystem-based aquaculture development with environmental conservation, offering a replicable framework for other regions facing similar challenges. This approach provides a pathway for achieving long-term sustainability in aquaculture, contributing to global food security and ecological resilience.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Integrating larval connectivity into the marine conservation decision‐making process across spatial scales - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Wahid Suherfian; La Sara; Iliana Chollett; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal connectivity is typically integrated into spatial conservation decisions at regional or national scales, but implementing agencies struggle with translating these methods to local scales. We used larval dispersal connectivity at regional (hundreds of kilometers) and local (tens of kilometers) scales to aid in design of networks of no‐take reserves in Southeast Sulawesi, Indonesia. We used Marxan with Connectivity informed by biophysical larval dispersal models and remotely sensed coral reef habitat data to design marine reserve networks for 4 commercially important reef species across the region. We complemented regional spatial prioritization with decision trees that combined network‐based connectivity metrics and habitat quality to design reserve boundaries locally. Decision trees were used in consensus‐based workshops with stakeholders to qualitatively assess site desirability, and Marxan was used to identify areas for subsequent network expansion. Priority areas for protection and expected benefits differed among species, with little overlap in reserve network solutions. Because reef quality varied considerably across reefs, we suggest reef degradation must inform the interpretation of larval dispersal patterns and the conservation benefits achievable from protecting reefs. Our methods can be readily applied by conservation practitioners, in this region and elsewhere, to integrate connectivity data across multiple spatial scales.

Comparing spatial conservation prioritization methods with site‐ versus spatial dependency‐based connectivity - Dominic Muenzel; Kay Critchell; Courtney Cox; Stuart J. Campbell; Raymond Jakub; Iliana Chollett; Nils Krueck; Daniel Holstein; Eric A. Treml; Maria Beger (Conservation Biology, 2023)
Larval dispersal is an important component of marine reserve networks. Two conceptually different approaches to incorporate dispersal connectivity into spatial planning of these networks exist, and it is an open question as to when either is most appropriate. Candidate reserve sites can be selected individually based on local properties of connectivity or on a spatial dependency‐based approach of selecting clusters of strongly connected habitat patches. The first acts on individual sites, whereas the second acts on linked pairs of sites. We used a combination of larval dispersal simulations representing different seascapes and case studies of biophysical larval dispersal models in the Coral Triangle region and the province of Southeast Sulawesi, Indonesia, to compare the performance of these 2 methods in the spatial planning software Marxan. We explored the reserve design performance implications of different dispersal distances and patterns based on the equilibrium settlement of larvae in protected and unprotected areas. We further assessed different assumptions about metapopulation contributions from unprotected areas, including the case of 100% depletion and more moderate scenarios. The spatial dependency method was suitable when dispersal was limited, a high proportion of the area of interest was substantially degraded, or the target amount of habitat protected was low. Conversely, when subpopulations were well connected, the 100% depletion was relaxed, or more habitat was protected, protecting individual sites with high scores in metrics of connectivity was a better strategy. Spatial dependency methods generally produced more spatially clustered solutions with more benefits inside than outside reserves compared with site‐based methods. Therefore, spatial dependency methods potentially provide better results for ecological persistence objectives over enhancing fisheries objectives, and vice versa. Different spatial prioritization methods of using connectivity are appropriate for different contexts, depending on dispersal characteristics, unprotected area contributions, habitat protection targets, and specific management objectives. Comparación entre los métodos de priorización de la conservación espacial con sitio y la conectividad espacial basada en la dependencia